Hand Grip Measure Tool Post-Stroke Patients - Ria Ramadhani; Endang Dian Setioningsih; Torib Hamzah (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2019)
Handgrip Dynamometer is a tool used to view the strength of the hand muscles post-stroke patients. In this study Handgrip Dynamometer created to look at the hand grip strength in real time and find out the hand grip strength criteria, there are three indicators: the criteria of mild, moderate or strong. Handgrip dynamometer using the Arduino Uno control over the entire system and Load Cell as a sensor. Load Cell Output will be boosted by Analog Signal conditioner HX711 and then processed in the microcontroller, then will be displayed on the LCD. Berdasarlan weight measurement results obtained by the result of error by 0% By comparison to using weights, sehingga can be concluded that the tool can be used according to its function.